Pengetahuan, Persepsi dan Sikap Generasi Muda Tentang Perubahan Iklim dan Pengaruhnya Terhadap Niat Perilaku Pro-Lingkungan - Dian Harmuningsih; Saul Ronald Jacob Saleky (LPPM ITK, 2017)
Climate change continues to occur and have an impact for the survival of mankind. Climate change is not only a natural phenomenon, but also includes contributions from the behavior of the human. Hence need for awareness and goodwill of all parties, especially the young generation, to reduce the impact of climate change. This study aimed to analyze the influence of factors of knowledge, perception and attitude towards pro-environmental behavior intention of the young generation. By using multiple regression analysis, the results of this study show that the factor of knowledge, perceptions and attitudes about climate change have a positive influence and significant to pro-environmental behavior intention of the young generation. Furthermore, of these factors, the perceptions of the climate change are factors that have a more dominant influence on the intention proenvironmental behavior of the young generation. Thus, in order to further grow and develop the intention of young people to behave in a pro-environment, for they need to be given opportunities and greater access to resources and information channels to increase their knowledge related to environmental strategic issues, especially climate change and its impacts, so with the knowledge that will shape their perceptions better on climate change and, in turn, will form a more empathetic attitude. For that, the one way can be used is to empower organizations where they are working as a means to increase knowledge, shape perceptions and attitudes and arouse their intentions to behave pro-environment, through the activity of an organized, planned and organized.